Alcalóides de Rutaceae: química e atividade biológica - Andrade, Márcio Roberto de (Universidade Federal de São Carlos, 2003)
This work describes the phytochemical study of two plant species Galipea bracteata and Ravenia infelix belonging to the family Rutaceae, aiming the isolation and structure determination of componds from leaves and branches of these plants. This work is also directed to the search of trypanocidal and leishmanicidal compounds from these plants. The following models were used to check the biological activities of the isolated compounds: antiparasitc activity - trypomastigote form of Trypanosoma cruzi in vitro , enzymatic inhibitory activity on gGAPDH (Glyceraldeyde 3- phosphate dehidrogenase) of T. cruzi and enzymatic inhibitory activity on APRT (Adheninephosphoribosyl- transferase) of Leishmania tarentolae. The leaves extract of G. bracteata afforded tirtheen quinoline alkaloids. Among these compounds seven have been described for the first time: 2-(3 ,4 -methylenedioxyphenylethyl)quinoline, 4- methoxy-2-(propan-1 -ona)quinoline (inedit), 4-methoxy-2-(1 ,2 -transepoxypentyl) quinoline (inedit), 4-methoxy-2-n-heptylquinoline, 2-(1 ,2 -transepoxypentyl) quinoline (inedit), 4-methoxy-2-(3 ,4 - methylenedioxyphenylethyl)quinoline, 4-methoxy-2-(1 ,2 -trans-epoxypropyl)quinoline (inedit), 4-methoxy-2-n-propylquinoline, 2-n-pentylquinoline, 2-(propan-1 - one)quinoline (inedit), 4-methoxy-2-(pentan-1 -one)quinoline (inedit), 2-(pentan-1 - one)quinoline (inedit), a mixture of steroids campesterol, stigmasterol and sitosterol, one furoquinoline alkaloid evolitrine, a mixture of seco-furoquinoline alkaloids Edimethylrhoifolinate and Z-dimethylrhoifolinate, a pentacylclic triterpene arborinol and norsesquiterpene 3,5-dihydromegastigma-6,7-diene-9-one. From the branches of R. Infelix were isolated the carbazole alkaloids: 3-methylcarbazole and girinimbin, the steroids: 7-oxo-stigmasterol and 7-oxo-sitosterol, the indol 3-carboxaldeheide and mixtures of amides: N-trans and N-cis-feruloyltyramine, and N-trans and-cis-pcumaroyltyramine. The pure compounds had their trypanocidal and leishmanicidal activities determined.
Alkaloids of rutaceae: chemistry and biological activity
Keywords: Química orgânica; Rutaceae; Alcalóides; Galipea bracteata; Ravenia infelix; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA